Benefits and drawbacks of open partial horizontal laryngectomies, Part B: Intermediate and selected advanced stage laryngeal carcinoma. (15th June 2015) - Succo, Giovanni; Crosetti, Erika; Bertolin, Andy; Lucioni, Marco; Arrigoni, Giulia; Panetta, Valentina; Sprio, Andrea E.; Berta, Giovanni N.; Rizzotto, Giuseppe
ABSTRACT: Background: Cancer of the larynx in the intermediate/advanced stage still presents a major challenge in terms of controlling the disease and preserving the organ. Among therapeutic options, open partial horizontal laryngectomy is proposed as a function‐sparing surgical technique. Methods: We analyzed the clinical outcomes of 555 patients with laryngeal cancer staged pT3 to pT4a who underwent open partial horizontal laryngectomy. Results: Five‐year overall survival (OS), disease‐free survival (DFS), locoregional control, local control, laryngectomy‐free survival, and laryngeal function preservation rates were 84.6%, 84.2%, 86.3%, 90.6%, 93.3%, and 91.2%, respectively. DFS, locoregional control, and laryngeal function preservation rates were significantly affected by pT4a staging (68.1%, 71.7%, and 78.0%, respectively), whereas pN+ influenced only DFS (≤72.6%) and locoregional control (≤79.6%). Conclusions: Open partial horizontal laryngectomy with a modular approach can be considered effective in terms of prognostic and functional results in intermediate‐stage and selected advanced‐stage laryngeal cancers, even with subglottic extension. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E649–E657, 2016